1979
DOI: 10.1111/j.1600-0447.1979.tb00254.x
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid hormones and TSH, prolactin and LH responses to repeated TRH and LRH injections in depressed patients

Abstract: Twelve patients with unipolar depressive disorders received 600 microgram of synthetic TRH or LRH, in a random order, for 3 days each. Placebo injections were given as two 3-day courses prior to and between the active treatments. Serum TSH, prolactin (Prl) and LH were measured by radioimmunoassays prior to the experiment as well as immediately before and 20 min after each injection. Serum T4 and T3 were determined by radioimmunoassays before the treatments and 24 h after the first two TRH injections. Serum T4 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

1981
1981
1991
1991

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(14 citation statements)
references
References 32 publications
1
13
0
Order By: Relevance
“…This is similar to the findings of Linnoila et al [2] and Orsulak et al [4], On the other hand, other studies on T3 in depressed patients reported it normal [3,9], Furthermore, Spratt et al [10] reported increased T3 and T4 levels in a series of 646 psychiatric patients that included depressed subjects.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…This is similar to the findings of Linnoila et al [2] and Orsulak et al [4], On the other hand, other studies on T3 in depressed patients reported it normal [3,9], Furthermore, Spratt et al [10] reported increased T3 and T4 levels in a series of 646 psychiatric patients that included depressed subjects.…”
Section: Discussionsupporting
confidence: 78%
“…Serum levels of total thyrox ine (TT4) and free thyroxine (FT4) in depressed patients have been described elevated, decreased, and normal [1][2][3][4], On the other hand, triiodothyronine (T3) levels in depressed patients were reported low [4] and normal [ …”
Section: Introductionmentioning
confidence: 99%
“…Inexplainable abnormal PRL titres in depression have been observed by other workers when PRL was studied around the clock [Mendlewicz et al, 1980] or by means of basal values taken only in the morning [Sachar et al. 1973;Maedaex al., 1975;Horrobin et al, 1976;Linnoila et al, 1979]. Besides, in monopolar depression PRL responses to insulin hypoglycemia, /-dopa, and thyrotropin-releasing hormone have been found within the normal ranges [Sachar et al, 1973;Ehrensing et al, 1974;Maeda et al, 1975;Brambilla et al, 1979;Ettigi and Brown, 1979], However, as it occurs also in the groups of Halbreich et al [1979] and Mendlewicz et al [1980], the PRL levels during the awake pe riod are higher and sleep levels are lower in our untreated monopolar depressed patients in respect to controls.…”
Section: Discussionmentioning
confidence: 46%
“…This secretory alteration is, how ever, unexplained. Up to now inconclusive PRL data have been obtained in depressed patients given TRH: mention of enhanced [22], normal [23] and in a few sub jects inhibited responses have been made [24][25][26][27][28], The blunting or the abolition of PRL response to TRH that we observed led us to regard PRL as an interesting bio logical index in depression, along with TSH. At variance with the data of Linkowski et al [27], which indicate an impairment of PRL response to TRH only in menopau sal depressed women, our findings seem to exclude an interference of ovarian function changes in the response.…”
Section: Discussionmentioning
confidence: 99%